64. Symphytosociological nomenclature: new proposals - Izco, Jesús (Lazaroa, 2014)
A new nomenclatural formula for vegetation series is proposed that is more closely in line with the commonly-usedforms of phytosociological nomenclature. The concept of facies associated to the appearance of a vegetation series is defended,and its advantages in mapping plant landscapes.